Database Application of Maternal Health Care Services in The Health District of Southern Timor District - Nixon Marthinus Lopo; Hari Basuki Notobroto; Santi Martini (Health Notions, 2017)
Maternal Mortality Rate (MMR) is still a problem in Indonesia. TTS Regency is one of the districts in NTT province with high MMR. Efforts through PWS-KIA include a system of recording and reporting of maternal health services into one of the important strategies in suppressing MMR. The problem is that data management is still done conventionally. With the manual process of course many problems arise in the management process in the work unit. Information technology support is more advanced, conventional data management ways can be replaced with information systems using a computer. Data management also becomes faster and easier to obtain accurate data to use as a basis for decision making in the prevention of health problems. The purpose of this research is to develop a database of maternal health services in TTS District Health Office to assist midwives in managing data on maternal health services at health care center. Activities undertaken in the development of this database include identification of ongoing recording and reporting systems, identification of data and information needs, database design, testing and evaluation. The database is developed using PHP-MySQL web-based applications. In carrying out the data base it is necessary to support the power to operate the data base, facilities with sufficient specification, increase the capacity of personnel regarding the database developed.Keywords: Database, Recording and Reporting System of Maternal Health Services